Traumatic-Induced Coagulopathy as a Systems Failure: A New Window into Hemostasis - Dobson, Geoffrey P.; Morris, Jodie L.; Davenport, Lisa M.; Letson, Hayley L. (Seminars in Thrombosis and Hemostasis, 2020)
Traumatic-induced coagulopathy (TIC) is often associated with significant bleeding, transfusion requirements, inflammation, morbidity, and mortality. This review considers TIC as a systems failure, not as a single-event manifestation of trauma. After briefly reviewing the meaning of TIC and the bewildering array of fibrinolysis phenotypes, we will discuss the role of platelets and fibrinogen in coagulopathy. Next, we will review the different TIC hypotheses and drill down to a single mechanistic domain comprising (1) thrombin's differential binding to thrombomodulin, (2) the expression of annexin II-S100A10 complex, and (3) the functional integrity of the endothelial glycocalyx. This triad forms the basis of the “switch” hypothesis of TIC. We will next address the potential limitations of current practice in treating a coagulation or fibrinolytic defect, and the next defect, and so on down the line, which often leads to what U.S. surgeon William C. Shoemaker considered “an uncoordinated and sometimes contradictory therapeutic outcome.” The treat-as-you-go approach using sequential, single-target treatments appears to be a by-product of decades of highly reductionist thinking and research. Lastly, we will present a unified systems hypothesis of TIC involving three pillars of physiology: the central nervous system (CNS)–cardiovascular system, the endothelial glycocalyx, and mitochondrial integrity. If CNS control of ventriculoarterial coupling is maintained close to unity following trauma, we hypothesize that the endothelium will be protected, mitochondrial energetics will be maintained, and TIC (and inflammation) will be minimized. The Systems Hypothesis of Trauma (SHOT) also helps to answer why certain groups of severely bleeding trauma patients are still dying despite receiving the best care. Currently, no drug therapy exists that targets the whole system.
Keywords: resuscitation; coagulopathy; glycocalyx; endothelium; shock; hemorrhage; ROTEM; TEG; fibrinolysis; injury